The Use Of Game-Based Learning Media On The Understanding Of Mathematics Concepts Of Elementary School Students - Erni Nurjanah; Ardi Cahyadireja; Rista Efendi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The problem in this study is the need for more understanding of students’ mathematical concepts at SDN Gegerbitung. Their mathematics learning scores still need to be higher than the KKM. This study aims to determine the effect of using Game-Based Learning on Elementary School Students. This research is a type of quantitative research using a quasi-experimental approach, the design in this study uses the Nonequevalent Control Group Design. The population in this research is all class III SDN Gegerbitung, with the first sample class IIIB totaling 20 students as the experimental class whose lessons use game-based learning and the second sample class IIIA totaling 20 students as the control class using conventional learning. Data on the ability to understand mathematical concepts were measured through a test instrument. To analyze the data in this study, a statistical test was used, namely the independent sample t-test. Based on the results of the t-test, the value of Sig = 0.003 <0.05, which means that there is a significant influence between the use of Game-Based Learning and Understanding of Mathematics Concepts for Elementary School Students. In addition, based on the results of the final test (posttest) obtained an average of 82.25 for the experimental class. At the same time, the control class received an average score of 72.50. This indicates that using Game Based Learning can improve students' understanding of mathematical concepts at SDN Gegerbitung for the 2021/2022 academic year.